2020
DOI: 10.3390/polym13010118
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Neuro-Fuzzy Inference System for Modelling the Effect of Slurry Impacts on PLA Material Processed by FDM

Abstract: In this research, the effect of water-silica slurry impacts on polylactic acid (PLA) processed by fused deposition modeling (FDM) is examined under different conditions with the assistance of an adaptive neuro-fuzzy interference system (ANFIS). Building orientation, layer thickness, and slurry impact angle are considered as the controllable variables. Weight gain resulting from water, net weight gain, and total weight gain are the predicting variables. Results uncover the accomplishment of the ANFIS model to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…With regard to additive manufacturing, in recent years, the application of machine learning and soft computing techniques are gaining a growing interest [ 23 ], as can also be observed in studies such as that of Saleh et al [ 24 ], which analyzed the effect of water-silica slurry impacts on polylactic acid (PLA), processed by fused deposition modelling (FDM), by using an ANFIS in which building orientation, layer thickness, and slurry impact angle were the inputs and weight gain resulting from water, net weight gain, and total weight gain were the outputs. In their study, a Taguchi orthogonal array was used for planning the experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to additive manufacturing, in recent years, the application of machine learning and soft computing techniques are gaining a growing interest [ 23 ], as can also be observed in studies such as that of Saleh et al [ 24 ], which analyzed the effect of water-silica slurry impacts on polylactic acid (PLA), processed by fused deposition modelling (FDM), by using an ANFIS in which building orientation, layer thickness, and slurry impact angle were the inputs and weight gain resulting from water, net weight gain, and total weight gain were the outputs. In their study, a Taguchi orthogonal array was used for planning the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, generalized bell membership functions and a Sugeno FIS were also considered in their study. Among their conclusions, the authors found that the ANFIS could adequately predict the effect of slurry impacts on PLA material processed by FDM [ 24 ]. Likewise, Kumar et al [ 25 ] employed a fuzzy inference system combined with the Taguchi philosophy for optimization of the FDM process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…FDM products are manufactured by extruding a semimolten filament material through an automatically controlled nozzle mounted in the machine head. The nozzle fuses and extrudes the material while the machine head is moving to deposit the layers of the part (Abdelaal, Heshmat and Abdelrhman, 2020;Peker et al, 2020;Saleh et al, 2021;Heshmat and Adel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, lack of lubrication during the process could decrease the surface finishing quality and there is no FE modelling for the process. Case hardening of the punch and die can be employed for increasing the surface hardness and in turn enhancing the cladding process [19][20] [21]. In the present work, a cladding process was applied between two tubes, Aluminium and copper tubes are used, using spherical punch with three different spherical tip diameters.…”
Section: Introductionmentioning
confidence: 99%